Study of the effect of culture mediums on the amino acid metabolites for Corynebacterium glutamicum using high‐speed micellar electrokinetic chromatography. Issue 20 (4th June 2019) - Wang, Wei; Bai, Ruiguang; Zhang, Huimin; Cai, Xiaoyu
Abstract: Corynebacterium glutamicum ( C. glutamicum ) is a well‐known workhorse for the industrial production of amino acids. Different carbon, nitrogen, and sulfur source may force the bacterium to produce specific metabolites. In this work, a method of high‐speed MEKC with LIF detection was developed to rapidly analyze the amino acid metabolites released by C. glutamicum, which is fed with different culture mediums. Corynebacterium glutamicum was cultured in microbial fuel cells to monitor its metabolism process and collect its metabolites. In the CE system, a microliter‐scale sample reservoir was designed and applied to perform tiny volume sample injection. With the assistance of microwave, the derivatization time for amino acids with FITC was greatly shortened to 6 min. Under the optimized condition, the eight candidate amino acids of metabolites could be rapidly separated within 2 min. The whole analysis process for real samples, from sampling to determination, could be shortened to less than 10 min. The results showed that C. glutamicum could produce additionall ‐lysine andl ‐valine as the metabolites when fed with glucose andl ‐methionine, respectively. The method proved that culture mediums used to feed C. glutamicum had great effect on the bacterium's metabolites.